2019
DOI: 10.1007/s10745-019-00083-x
|View full text |Cite
|
Sign up to set email alerts
|

Forest Ecosystem Services and Local Communities: Towards a Possible Solution to Reduce Forest Dependence in Bach Ma National Park, Vietnam

Abstract: Conservation of protected areas is likely to be challenging in the long term if the dependence of local communities on natural resources is not measured appropriately. We investigated forest ecosystem services utilized by communities living around the Bach Ma National Park, Vietnam, and examined their spatial distributions through the integration of data from interviews, participatory mapping, and GIS analysis. The results suggest that provisioning services are crucial to the local livelihoods, and especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…On the other hand, agricultural and forestry practitioners who depend on material output seek higher added-value industrial activities under PA management. This trend of ecological and cultural valorisation in protected area is becoming common [55][56][57] and is also hinted by the results that middle-and high-income families that tend to engage in tourism operating. Moreover, tea farmers and tourism operators prioritised eco-tourism and tea, respectively, indicating their expectation of livelihood diversification based on the combination of provisioning and culture services, which can be conservation-compatible.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, agricultural and forestry practitioners who depend on material output seek higher added-value industrial activities under PA management. This trend of ecological and cultural valorisation in protected area is becoming common [55][56][57] and is also hinted by the results that middle-and high-income families that tend to engage in tourism operating. Moreover, tea farmers and tourism operators prioritised eco-tourism and tea, respectively, indicating their expectation of livelihood diversification based on the combination of provisioning and culture services, which can be conservation-compatible.…”
Section: Discussionmentioning
confidence: 94%
“…Das (2000) observed that conservation activities in common property resource is weak in labor constrained setting. The finding also suggests that large households, as indicated by Hong and Saizen (2019), are involved in indigenous forest management practices for NTFP management and conservation because of their need for forest products to ensure their livelihoods. Also, the finding that the number of years spent in school is negatively and significantly associated with the use of indigenous protective mechanisms suggests that educated people who are pragmatic in their thinking will not rely on the efficacy of indigenous protective mechanisms for forest protection.…”
Section: Discussionmentioning
confidence: 97%
“…Although the finding shows that indigenous knowledge increases with age, there is no explicit agreement regarding the influence of age on the practice of harvesting of forest products. While Mamo et al (2007) and Coulibaly-Lingani et al (2009) found that young people collect forest products more than older people, Hong and Saizen (2019) found that older people collect more forest products than younger people.…”
Section: Conceptual Frameworkmentioning
confidence: 97%
“…The rest of the forest users include people living in urban and rural areas. Ecosystem services derived from the forest include fuelwood, fiber, construction material, herbal medicine, honey, fodder and water among other services [2] [3]. According to Jenkins & Schaap [1], forests are an important income generator especially to rural families in Africa, Asia and Latin America.…”
Section: Introductionmentioning
confidence: 99%